Coral record of southeast Indian Ocean marine heatwaves with intensified Western Pacific temperature gradient - Zinke, Jens; Hoell, A.; Lough, J.; Feng, M.; Kuret, A.; Clarke, H.; Ricca, V.; Rankenburg, K.; McCulloch, M. (Nature Publishing Group, 2015)
Increasing intensity of marine heatwaves has caused widespread mass coral bleaching events, threatening the integrity and functional diversity of coral reefs. Here we demonstrate the role of inter-ocean coupling in amplifying thermal stress on reefs in the poorly studied southeast Indian Ocean (SEIO), through a robust 215-year (1795-2010) geochemical coral proxy sea surface temperature (SST) record. We show that marine heatwaves affecting the SEIO are linked to the behaviour of the Western Pacific Warm Pool on decadal to centennial timescales, and are most pronounced when an anomalously strong zonal SST gradient between the western and central Pacific co-occurs with strong La Niña's. This SST gradient forces large-scale changes in heat flux that exacerbate SEIO heatwaves. Better understanding of the zonal SST gradient in the Western Pacific is expected to improve projections of the frequency of extreme SEIO heatwaves and their ecological impacts on the important coral reef ecosystems off Western Australia.